2009
DOI: 10.1002/joc.1841
|View full text |Cite
|
Sign up to set email alerts
|

Sunshine and synoptic cloud observations at Ebro Observatory, 1910–2006

Abstract: ABSTRACT:The aim of this study is to characterize the evolution of the number of bright sunshine hours and cloudiness at Ebro Observatory. Sunshine and synoptic cloud observations, extending over almost a century, are available from the Ebro Observatory in the north-east of Spain. Here, we analyse these time series and find a strong decadal variability in the duration of bright sunshine hours since 1910, but without a statistically significant long-term trend. A comparison with sunshine records from other Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, it is worth noticing that if the Granada series is analyzed independently from our dataset, the linear trend for the 1908-1953 period is also significant and negative (−1.6 % per decade) in agreement with Henderson-Sellers (1986a). Equally, the reported increase in TCC at a northern station of Spain (Curto et al, 2009), which is not included in the current study, is in line with our findings, although the rate of increase for this specific station is considerably higher than the one provided in our results. This fact, together with the decreasing trend found at individual stations, such as in southern Spain (i.e.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, it is worth noticing that if the Granada series is analyzed independently from our dataset, the linear trend for the 1908-1953 period is also significant and negative (−1.6 % per decade) in agreement with Henderson-Sellers (1986a). Equally, the reported increase in TCC at a northern station of Spain (Curto et al, 2009), which is not included in the current study, is in line with our findings, although the rate of increase for this specific station is considerably higher than the one provided in our results. This fact, together with the decreasing trend found at individual stations, such as in southern Spain (i.e.…”
Section: Discussionmentioning
confidence: 52%
“…Finally, other studies focusing only on one station reported an increase in TCC since the late 19th or the beginning of the 20th centuries: i.e. in Cracow, Poland (Matuszko, 2003;Lewik et al, 2010); in Armagh, Ireland (Pallé and Butler, 2002b); and in Northeastern Spain (Curto et al, 2009). In this latter study, the authors reported a change of around 2 oktas (i.e.…”
Section: A Sanchez-lorenzo Et Al: Increasing Cloud Cover In the 20tmentioning
confidence: 63%
“…[], Figure 10). Therefore, a large literature record relating these two magnitudes and studying their annual, seasonal, and monthly evolution is available [e.g., Fox , ; Angell et al ., ; Angell , ; Jones and Henderson‐Sellers , ; Weber , ; Palle and Butler , 2001; Curto et al ., ; Matuszko , ]. But this relationship is not always simple and linear and can be affected by several factors, such as changes in atmospheric transparency resulting from aerosols or changes in the properties of clouds.…”
Section: Evidence Of Aerosol/turbidity Effects On Sunshine Duration Mmentioning
confidence: 99%
“…In fact, our meteorological archives date back to the year 1880. As a result of this, we have a long series of meteorological data that allows us to carry out climate studies of the Ebro and, by extension, the Mediterranean region (Curto et al, 2008). Among all these data, there is a historical series of atmospheric visibility.…”
Section: Locationmentioning
confidence: 99%